Preparation and characterization of Silicalite-1 zeolites with high manganese contents from mechanochemically pretreated reactants1. Issue 11 (21st March 2015) - Iida, Takayuki; Sato, Mitsutaka; Numako, Chiya; Nakahira, Atsushi; Kohara, Shinji; Okubo, Tatsuya; Wakihara, Toru
<x xml:space="preserve">Abstract</x> Silicalite-1 zeolites with high manganese contents isomorphously incorporated within the framework were synthesized by using mechanochemical pretreatment.